Penyuluhan Pemberdayaan Masyarakat Tentang Pemasangan dan Pelepasan Iud di Desa Sidodadi Kecamatan Biru Biru Kabupaten Deli Serdang Tahun 2021 - Desi Anggraini; Dwi Ris Hasanah (Journal of Community Development, 2022)
Indonesia's population has increased from 265,015,300 people in 2018 to 268,074,600 people in 2019. The government created a program to intervene in the problem of uncontrolled population growth, namely the family planning (KB) program. The Long-Term Contraceptive Method (MKJP) with implants is one of the leading contraceptives from BKKBN. MKJP is the government's effort to reduce population growth. The purpose of this service is to help the government to achieve coverage of long-term contraceptive use through free counseling and installation. The results of a brief interview with family planning acceptors, most of them chose pills and injections because they were afraid to use implants and IUDs. The fear is caused by the method of installation and the side effects that can be caused. The results that have been achieved in this service are 56% of the family planning acceptor groups in the area are interested in being fitted with MHJP, which shows the success of this activity. We hope that in the future this coverage can continue to increase. We will continue to run this program by continuing to provide counseling and health education to family planning acceptors so that they can clearly illustrate the effectiveness of MHJP is greater than non-MKJP by 99.4%.